2005
DOI: 10.2337/diabetes.54.12.3517
|View full text |Cite
|
Sign up to set email alerts
|

Individual Mice Can Be Distinguished by the Period of Their Islet Calcium Oscillations

Abstract: Pulsatile insulin secretion in vivo is

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
84
1

Year Published

2006
2006
2014
2014

Publication Types

Select...
5
4

Relationship

5
4

Authors

Journals

citations
Cited by 88 publications
(98 citation statements)
references
References 52 publications
13
84
1
Order By: Relevance
“…For example, hyperglycemic clamps, in which glucose is infused at a variable rate to maintain hyperglycemia relative to fasting glucose, can be used to assess endogenous pancreatic function in vivo 2,20,21 . The measurement of first phase insulin secretion during this test requires frequent acquisition of blood samples (i.e every 2-5 min), which is not feasible when obtaining samples from the tip of the tail.…”
Section: Discussionmentioning
confidence: 99%
“…For example, hyperglycemic clamps, in which glucose is infused at a variable rate to maintain hyperglycemia relative to fasting glucose, can be used to assess endogenous pancreatic function in vivo 2,20,21 . The measurement of first phase insulin secretion during this test requires frequent acquisition of blood samples (i.e every 2-5 min), which is not feasible when obtaining samples from the tip of the tail.…”
Section: Discussionmentioning
confidence: 99%
“…For measurements of firstand second-phase insulin secretion, islets were incubated in 3 mM glucose KRB plus 30 mM KCl for 5 minutes, followed by incubation in 28 mM glucose KRB for an additional 10 minutes. Intracellular calcium measurements were made using the ratiometric calcium dye fura-2 (63). Islets were loaded with 3 μM fura-2-acetoxymethylester (fura-2 AM) for 30 minutes, transferred to a low-volume chamber (Warner Instruments), mounted on the stage of an Olympus BX51WI fluorescence microscope, and subsequently perifused with 3 mM followed by 28 mM glucose KRB delivered by a peristaltic pump (Gilson) maintained at 37°C with an in-line heater (Warner Instruments).…”
Section: Methodsmentioning
confidence: 99%
“…This observation supports our previous findings regarding the importance of oscillations to normal islet health, 8,10 however, it should be noted that ideally oscillations should be recorded in steady-state glucose to prevent transient states in their oscillatory periods. 18,19 Two separate trials were conducted, one with untreated islets labeled with CTR and another with cytokine-treated islets labeled with CTR. In each trial, the cytokine-treated islets showed a substantially reduced GSCa regardless of labeling.…”
Section: ©2 0 1 1 L a N D E S B I O S C I E N C E D O N O T D I S Tmentioning
confidence: 99%